2000
DOI: 10.1056/nejm200002243420806
|View full text |Cite|
|
Sign up to set email alerts
|

Physicians' Experiences with the Oregon Death with Dignity Act

Abstract: Our data indicate that in Oregon, physicians grant about 1 in 6 requests for a prescription for a lethal medication and that 1 in 10 requests actually result in suicide. Substantive palliative interventions lead some--but not all--patients to change their minds about assisted suicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
250
2
6

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 311 publications
(262 citation statements)
references
References 17 publications
4
250
2
6
Order By: Relevance
“…The authors concluded that behind each decision and request for euthanasia lay 'hidden existential yearnings for connectedness, care, and respect'. Other similar studies [3,63,64] conducted in Canada and the United States have found that the WTHD becomes less strong when the patient perceives a degree of hope in the treatment and care being received.…”
Section: Temporal Stability Of the Wthdmentioning
confidence: 99%
“…The authors concluded that behind each decision and request for euthanasia lay 'hidden existential yearnings for connectedness, care, and respect'. Other similar studies [3,63,64] conducted in Canada and the United States have found that the WTHD becomes less strong when the patient perceives a degree of hope in the treatment and care being received.…”
Section: Temporal Stability Of the Wthdmentioning
confidence: 99%
“…11 Family members did not endorse the importance of any of these factors, consistent with the findings of other studies. [2][3][4][5]16 . It is true,…”
Section: Discussionmentioning
confidence: 99%
“…1 Because PAD is rare, most information about individuals who have received prescriptions for lethal medications under the law has come through health care professionals, including physicians and hospice workers who have cared for requesting patients. [2][3][4][5] Oregon health care professionals generally agree that patients make these requests in an attempt to maintain control and diminish dependence on others. Health professionals, however, may lack intimate knowledge of the requesting patient's reasons and values.…”
mentioning
confidence: 99%
“…1 In a survey conducted two years after the Death with Dignity Act took effect, physicians reported very few requests under the law, and 46 % of patients who made a request changed their minds after physician interventions. 2 Oregon continues to rank among the top states in the country in the provision of excellent palliative care, 3 and utilization of the Death with Dignity Act remains low.…”
mentioning
confidence: 99%